Institutional Arrangements for the Promotion of Regional Integration of Electricity Markets : International Experience - Oseni, Musiliu O.; Pollitt, Michael G. (World Bank, Washington, DC, 2014)
This paper focuses on the institutional arrangements needed for facilitating regional electricity cooperation. The paper begins by discussing the theory of international trade cooperation in electricity, with a view to discussing what preconditions might be important in facilitating wide area trading across national borders. It then discusses two sets of case studies. The first set focuses on three regional developing country power pools -- the Southern African Power Pool, the West African Power Pool, and the Central American Power Market. The second set focuses on three regional power pools in more developed countries -- one in the United States, the Single Electricity Market in Ireland, and the South East Europe market. These cases highlight the potential and difficulty of having cross-jurisdictional power pools. In the light of the theory and evidence presented, key lessons are drawn in the areas of preconditions for trading, necessary institutional arrangements, practicalities of timetabling, reasons to be hopeful about future prospects, and suggestions for future research.